Glue Genes Are Subjected to Diverse Selective Forces during Drosophila Development. (12th November 2021) - Borne, Flora; Kulathinal, Rob J; Courtier-Orgogozo, Virginie
Abstract: Molecular evolutionary studies usually focus on genes with clear roles in adult fitness or on developmental genes expressed at multiple time points during the life of the organism. Here, we examine the evolutionary dynamics of Drosophila glue genes, a set of eight genes tasked with a singular primary function during a specific developmental stage: the production of glue that allows animal pupa to attach to a substrate for several days during metamorphosis. Using phenotypic assays and available data from transcriptomics, PacBio genomes, and sequence variation from global populations, we explore the selective forces acting on glue genes within the cosmopolitan Drosophila melanogaster species and its five closely related species, D. simulans, D. sechellia, D. mauritiana, D. yakuba, and D. teissieri . We observe a three-fold difference in glue adhesion between the least and the most adhesive D. melanogaster strain, indicating a strong genetic component to phenotypic variation. These eight glue genes are among the most highly expressed genes in salivary glands yet they display no notable codon bias. New copies of Sgs3 and Sgs7 are found in D. yakuba and D. teissieri with the Sgs3 coding sequence evolving rapidly after duplication in the D. yakuba branch. Multiple sites along the various glue genes appear to be constrained. Our population genetics analysis in D. melanogaster suggests signals of local adaptive evolution for Sgs3, Sgs5, and Sgs5bis and traces of selective sweeps for Sgs1, Sgs3, Sgs7, and Sgs8 . Our work shows that stage-specific genes can be subjected to various dynamic evolutionary forces.